Kinetic Behaviour of Free Lipase and Mica-Based Immobilized Lipase Catalyzing the Synthesis of Sugar Esters - Zaidan, UH; Rahman, MBA; Othman, SS; Basri, M; Abdulmalek, E; Abd Rahman, RNZR; Salleh, A (Taylor & Francis Ltd, 2024)
The utilization of natural mica as a biocatalyst support in kinetic investigations is first described in this study. The formation of lactose caprate from lactose sugar and capric acid, using free lipase (free-CRL) and lipase immobilized on nanoporous mica (NER-CRL) as a biocatalyst, was evaluated through a kinetic study. The apparent kinetic parameters, K-m and V-max, were determined by means of the Michaelis-Menten kinetic model. The Ping-Pong Bi-Bi mechanism with single substrate inhibition was adopted as it best explains the experimental findings. The kinetic results show lower K-m values with NER-CRL than with free-CRL, indicating the higher affinity of NER-CRL towards both substrates at the maximum reaction velocity V-max,V-app > V-max). The kinetic parameters deduced from this model were used to simulate reaction rate data which were in close agreement with the experimental values.